(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Characteristics and Current status of infusion chamber use at the On-Demand Treatment Department, K Hospital. Materials and methods: Cross-sectional study of 74 patients diagnosed with cancer and treated at K Hospital. All patients were placed with subcutaneous infusion chambers at the On-Demand Treatment Department, K Hospital. Results: Patients had an average age of 56.4. The median BMI was 21. The majority of patients understood the role and operation of the infusion chamber, accounting for 95.9%. The average time from the day of infusion chamber placement to the day of outpatient treatment was 2.71 ± 5 days. The average time from the day of infusion chamber placement to the day of starting to use the chamber was 8.54 ± 9.01 days. The proportion of patients receiving infusion on the day of infusion chamber placement: 4/74, accounting for 5.4%. The proportion of patients receiving infusion 1 day after infusion chamber placement: 9/74, accounting for 12.2%. Rate of patients infused within 1-3 days after infusion chamber placement: 25/74, accounting for 33.8%. Rate of patients discharged on the day of infusion chamber placement: 48/74, accounting for 64.9%. Average time of infusion chamber use: 4.21 ± 4.45 days. Conclusion: Our study did not record any complications in 74 patients with infusion chambers during the 9-month follow-up period; only 1 patient had an interruption in the infusion process due to needle displacement on the 2nd day of the treatment cycle.